MILITARY ARTIFICIAL INTELLIGENCE AND NEW CONFIGURATIONS IN THE GULF STATE: IRAN MISSILE ATTACK ON ISRAEL - Faruq Alkafi; Munawar Ahmad (CMES (Center of Middle Eastern Studies), 2025)
This research analyzes the impact of the integration of artificial intelligence (AI) in Iran's missile technology on regional security dynamics and changes in the geopolitical configuration in the Middle East, especially after Iran's missile attack on Israel in October 2024. Through a post-structuralist approach, this study highlights the role of AI technology in changing the geopolitical reconfiguration in the Middle East. Iran successfully used advanced technologies, such as the Fattah hypersonic missile, which was able to penetrate Israel's Iron Dome defense system. The research found that Iran's advances in AI integration technology triggered the formation of new strategic alliances, such as cooperation between Israel, the United States and the Gulf states. Conversely, Iran's technological advancements attract collaboration from countries such as Russia and China. With a systematic analysis of the literature, this research provides important insights into how AI can change regional security dynamics and global perceptions of Iran as a military technology actor to reckon with.